Experimental Study on the Sun Tracking Ability of a Spherical Solar Collector. (January 2016) - Gaspar, Ferenc; Deac, Teodora; Tutunaru, Lucian V. Fechete; Moldovanu, Dan
Abstract: The present paper describes an experimental investigation on a spherical shape and flat plate absorber exposed to sun without cover. The temperature of both absorbing surface has been measured during the test day, from sunrise to sunset. Temperature distribution has been analyzed using a thermal camera. Experimental results show a good correlation between measured temperatures on the absorbing surfaces and values of the incident solar radiation measured with a fixed and a sun tracking pyranometer. The spherical absorbing surface is behaving like a sun tracking surface, during the day a hemisphere is exposed to sun and the other hemisphere is shaded. The overall daily average temperature on the spherical absorber is smaller than on the flat plate absorber, suggesting that the spherical absorber is not efficient as a solar radiation capturing surface.